2019
DOI: 10.1101/840405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remodeling of Crossbridges Controls Peptidoglycan Cross-linking Levels in Bacterial Cell Walls

Abstract: Cell walls are barriers found in almost all known

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…[28][29][30][31][32][33] Yet, single D-amino acid PG probes cannot interrogate how the stem peptide structure (or its many chemical modifications) can control PG crosslinking or processing. We 34,35 , and others [36][37][38][39] , have recently demonstrated that fluorescently tagged structural mimics of nascent TP substrates can be crosslinked into the growing PG scaffold of live cells, thus hijacking the cell wall machinery (Scheme 2B). Indeed, we have shown that penta-, tetra-, and tri-peptides that are analogs of the PG stem peptide are accepted by TPs to varying extents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33] Yet, single D-amino acid PG probes cannot interrogate how the stem peptide structure (or its many chemical modifications) can control PG crosslinking or processing. We 34,35 , and others [36][37][38][39] , have recently demonstrated that fluorescently tagged structural mimics of nascent TP substrates can be crosslinked into the growing PG scaffold of live cells, thus hijacking the cell wall machinery (Scheme 2B). Indeed, we have shown that penta-, tetra-, and tri-peptides that are analogs of the PG stem peptide are accepted by TPs to varying extents.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that penta-, tetra-, and tri-peptides that are analogs of the PG stem peptide are accepted by TPs to varying extents. 34,35 However, to this point we had been unable to investigate the role of m-DAP (and its modifications) because of the challenge in building m-DAP containing peptides.…”
Section: Introductionmentioning
confidence: 99%